Metal load assessment in patient pulmonary lavages: towards a comprehensive mineralogical analysis including the nano-sized fraction. Issue 9 (26th November 2017) - Forest, Valérie; Vergnon, Jean-Michel; Guibert, Cyril; Bitounis, Dimitrios; Leclerc, Lara; Sarry, Gwendoline; Pourchez, Jérémie
Abstract: Mineralogical analyses of clinical samples have been proved useful to identify causal relationship between exposure to airborne particles and pulmonary diseases. The most striking example is asbestosis where the assessment of asbestos bodies in patient lung samples has allowed defining values specific of pathologies. However, this type of analyses only considers the micro-sized fraction of the particles, neglecting the specific impact of nano-sized particles which have been otherwise shown to be reactive and able to induce biological effects. Similarly, in nanotoxicology, the mineralogical analysis of pulmonary fluids could be used as an indicator of exposure to inhaled nanoparticles and could help investigations on the relationship between exposure to these nanoparticles and lung diseases. We designed this study first to demonstrate the technical feasibility of this approach, then to get a clear picture of the metals present, and in what form, in patient lungs and finally to determine if indeed it is worth investigating separately the micro, sub-micro and nano fractions. Broncho-alveolar lavages were recovered from 100 patients suffering from interstitial lung diseases. A protocol was specifically developed to isolate three fractions containing respectively microparticles, sub-microparticles and nanoparticles with ions. The metal content in each fraction was qualitatively and quantitatively characterized. Results showed significant differences between the three fractions in terms of metal load confirming that the separate analysis of the fractions is relevant. It also means that the assessment of the micro-sized fraction alone, as commonly done in clinical practice, only gives a partial view of the mineralogical analysis.